The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s43045-020-00031-2
|View full text |Cite
|
Sign up to set email alerts
|

P300 cognitive assessment in patients with first-episode psychosis: a prospective case-control study

Abstract: Background: Several studies using event-related potential (ERP) methods have reported a relationship between the cognitive dysfunction of patients with psychosis and P300 latency and amplitude. P300 follow-up studies in patients with schizophrenia receiving antipsychotic treatment revealed that the P300 amplitudes were increased while other studies showed limited changes in the P300 amplitude even after antipsychotics use. Results: We found that at the first presentation, all patients' groups have significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Regarding the P3a latency just one study of those mentioned above highlighted a delayed P3a latency in FES subjects ( 213 ), while all other studies did not identify any alteration in P3a latency, in FEP, FES and HR subjects ( 68 , 163 , 188 , 189 , 196 , 206 , 207 , 209 , 213 215 ).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Regarding the P3a latency just one study of those mentioned above highlighted a delayed P3a latency in FES subjects ( 213 ), while all other studies did not identify any alteration in P3a latency, in FEP, FES and HR subjects ( 68 , 163 , 188 , 189 , 196 , 206 , 207 , 209 , 213 215 ).…”
Section: Resultsmentioning
confidence: 93%
“…With regard to the P3b latency, two studies reported an increase of this EEG measure in FEP ( 215 , 229 ), while other studies did not detect any abnormalities of this feature in FEP, FES ( 162 , 163 , 165 , 167 , 172 , 213 , 216 219 , 221 , 222 , 224 , 227 , 230 232 ), and HR subjects ( 68 , 163 , 165 , 168 , 169 , 227 , 228 ), as compared to HCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a pilot study evaluated an evoked potential as a marker of response, and suggested that olanzapine was able to restore the normal features of P300, which has a lower amplitude and a prolonged latency in SZ 121 .…”
Section: Discussionmentioning
confidence: 99%